Expression of bovine mitochondrial tRNASer GCU derivatives in Escherichia coli. - Hayashi, I (1997)
By replacing a stretch of five A-U base pairs in the acceptor stem with G-C pairs, mitochondrial tRNA-SerGCU lacking a D arm could be expressed in Escherichia coli cells in considerable amounts. The expressed tRNA with no modified nucleoside was serylated in vitro with the mitochondrial enzyme. The tRNASerGCU derivatives carrying identity elements for alanine tRNA and the related anticodons were expressed. However, this expression event did not affect cell growth, probably because the expression started from the late log phase, which suggests that these mitochondrial tRNA derivatives are not involved in E.coli gene expression systems. Although there are some restrictions in the secondary structure of tRNAs that can be expressed by this method, it could prove useful for preparing large amounts of heterologous tRNAs in vivo.